Metformin metabolic and vascular effects in normal weight hyperinsulinemic polycystic ovary syndrome patients treated with contraceptive vaginal ring. A pilot study. (1st December 2020) - Battaglia, Cesare; Battaglia, Bruno; Casadio, Paolo; Rizzo, Roberta; Artini, Paolo G.
Abstract: Purpose: The aim of this longitudinal, controlled, and retrospective pilot study was to assess how metformin, associated with a contraceptive vaginal ring, may influence lipid and carbohydrate metabolism, and surrogate markers of arterial function in normal weight polycystic ovary syndrome patients. Material and Methods: Among 28 lean patients, 15 were treated with vaginal ring plus metformin and 13 women with only vaginal ring. The effects were assessed after six months. The patients were submitted to evaluation of lipid and carbohydrate metabolism; Doppler analysis of ophthalmic artery; brachial artery flow-mediated vasodilatation; and oral glucose tolerance test. Results: After six months, the fasting insulin, glucose/insulin ratio, and homeostatic model assessment estimates for insulin resistance were significantly improved in metformin group. The ophthalmic artery pulsatility index did not significantly improve in either group. The brachial artery vasodilation was better in metformin treated patients. Conclusion: Metformin, associated with vaginal ring, improves the insulin and carbohydrate metabolism. This, associated with the significant improvements of surrogate markers of arterial function, may be responsible of a slight possible cardiovascular and cerebrovascular protective effect.